2013
DOI: 10.1155/2013/327604
|View full text |Cite
|
Sign up to set email alerts
|

Brain Hypothermic Therapy Dramatically Decreases Elevated Blood Concentrations of High Mobility Group Box 1 in Neonates with Hypoxic-Ischemic Encephalopathy

Abstract: Background. According to the Consensus 2010 of the International Liaison Committee on Resuscitation (ILCOR), children with moderate to severe hypoxic-ischemic encephalopathy (HIE) should receive brain hypothermic therapy (BHT) after successful resuscitation. Elevated high mobility group box 1 (HMGB1) in the blood at the early stage of brain ischemia-reperfusion injury has been suggested to be involved in the release of various inflammatory cytokines. Methods. In total, 21 neonates plasma HMGB1 concentration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…A line of evidence supports this hypothesis that the levels of HMGB1 are significantly lower in the blood of HIE infants treated with TH compare to that of untreated HIE infants (Nakamura et al , 2013). The activation of Janus kinase 2/STAT3 signaling pathway mediated by IL-6 results in expression of a series of genes involved in inflammation and apoptosis.…”
Section: Bench To Bedside: Promising Anti-inflammatory/immunomodulmentioning
confidence: 67%
“…A line of evidence supports this hypothesis that the levels of HMGB1 are significantly lower in the blood of HIE infants treated with TH compare to that of untreated HIE infants (Nakamura et al , 2013). The activation of Janus kinase 2/STAT3 signaling pathway mediated by IL-6 results in expression of a series of genes involved in inflammation and apoptosis.…”
Section: Bench To Bedside: Promising Anti-inflammatory/immunomodulmentioning
confidence: 67%
“…It has been reported that cerebral ischemia can upregulate serum HMGB1 to stimulate the release of TNFα, IL-6, and other inflammatory factors to induce inflammation, which will contribute to cerebral ischemic injury (Yang et al 2010). Certain HMGB1 inhibitors or some physical methods can attenuate injuries caused by cerebral ischemia reperfusion or neonatal hypoxic-ischemic encephalopathy (Nakamura et al 2013;Rickenbacher et al 2014;Wang et al 2012). Furthermore, previous studies have suggested that there would be a certain relationship between HMGB1 and autophagy (Kang et al 2011;Thorburn et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Production of MMP-916) and free radicals [17,18] and resulting damage to the BBB [19] has been reported to be the pathophysiology in acute encephalopathy. HMGB1 is also a good marker to help predict the outcome in neurological damage [20,21].…”
Section: Discussionmentioning
confidence: 99%